2017
DOI: 10.1590/s0102-865020170110000007
|View full text |Cite
|
Sign up to set email alerts
|

Topical action of Buriti oil (Mauritia flexuosa L.) in myositis induced in rats

Abstract: Results: The neutrophil number there was statistically significant difference, after 7 and 14 days, between groups C and MI (p <0.001) (p<0.01). The group MT there was a significant difference in relation to MI group in both experimental times with (p<0.001). The number of fibroblasts in the 14 days showed that when comparing the groups M and MT the differences were also significant (p<0.001). As for the DLL, in 7 days, there was a significant difference between group C and MI group (p <0.001). When considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study to evaluate the topical action of buriti oil in induced myositis in rats, Barbosa et al [ 60 ] observed the effect of administering 0.5 ml of buriti oil in the posterior region of the right gastrocnemius muscle of the animals for 7 and 14 days, after induction of myositis by injection of 0.2 ml 1 % acetic acid with a hypodermic needle and insulin syringe in the right gastrocnemius muscle. The following treatments were performed in 36 male rats divided into three groups: control group, induced myositis group, and induced myositis group treated with buriti oil.…”
Section: Biological Effects Of Fruits Of Amazonian Palm Treesmentioning
confidence: 99%
“…In another study to evaluate the topical action of buriti oil in induced myositis in rats, Barbosa et al [ 60 ] observed the effect of administering 0.5 ml of buriti oil in the posterior region of the right gastrocnemius muscle of the animals for 7 and 14 days, after induction of myositis by injection of 0.2 ml 1 % acetic acid with a hypodermic needle and insulin syringe in the right gastrocnemius muscle. The following treatments were performed in 36 male rats divided into three groups: control group, induced myositis group, and induced myositis group treated with buriti oil.…”
Section: Biological Effects Of Fruits Of Amazonian Palm Treesmentioning
confidence: 99%
“…More specifically, with pequi (Caryocar brasiliense) and buriti (Mauritia flexuosa L.) fruits, which are used in the region with different purposes such as human and animal feeding [14,15] , cosmetic and medicinal uses [16] . The fundamental importance in its composition is the abundance in unsaturated fatty acids, with the predominance of oleic acid, between 50-80% in mass, and also, the presence of tocopherols and carothenoids [11,14,15] .…”
Section: Introductionmentioning
confidence: 99%